Psychoeducational preventive treatment for women at risk of postpartum depression: study protocol for a randomized controlled trial, PROGEA. Issue 1 (December 2017) - Ugarte, Amaia; López-Peña, Purificación; Vangeneberg, Carmen; Royo, Julia; Ugarte, Maria; Compains, Maria; Medrano, Maria; Toyos, Nerea; Lamo, Edurne; Dueñas, Maria; González-Pinto, Ana
Abstract Background Postpartum depression is a disease with a prevalence of 20% that has deleterious consequences not only for the mother but also for the baby and can cause delays in physical, social and cognitive development. In this context, the European Union Committee on Public Health has declared it essential that preventative measures are taken by centres providing care for women with a multidisciplinary approach. PROGEA is a multicentre, single-blind randomized, 3-year, longitudinal clinical trial aiming to evaluate the efficacy of a psychoeducational programme in preventing postpartum depression in at-risk women, based on a range of clinical variables, and explore prognostic factors. This paper describes the methods and rationale behind the study. Methods We will study women receiving treatment as usual plus a psychoeducation cognitive behavioural therapy (CBT)-based intervention and a control group receiving only treatment as usual. The sample will be recruited from an incidental sampling of pregnant women in two health regions. We will recruit 600 women in the third trimester of pregnancy who consent to take part in the study. Almost half of the women, about 280, would be expected to have some risk factors for postpartum depression. All those found to have risk factors will be evaluated, and we estimate that a quarter will be classified as at-risk of developing postpartum depression as measured with the Edinburgh Postnatal Depression Scale. This subset will be randomly allocated to receive treatment as usual with or without the CBT intervention. Six sessions of CBT (1 individual and 5 group) will be offered by a psychologist. Discussion Findings from this study will be used to design a definitive study that will examine the clinical and cost-effectiveness of the CBT-based intervention in improving the mood of women in the postpartum period. Trial Registration ClinicalTrials.gov Identifier:NCT02323152 ; Date: December 2014.